How do dinosaurs learn to be kind? - Yolen, Jane; Teague, Mark (New York : Scholastic Press, 2023)
It is not always easy for a dinosaur to learn how to be kind, but with a little practice, and keeping other people firmly in mind, he can become a one-of-a-kind, very kind dinosaur.
K-3
AD500L
Keywords: Dinosaurs -- Juvenile fiction; Kindness -- Juvenile fiction; Thoughtfulness -- Juvenile fiction; Dinosaurs -- Fiction; Kindness -- Fiction; Thoughtfulness -- Fiction; Conduct of life -- Fiction; Stories in rhyme; Animal fiction